Potency of antigenic and serologic tests based on CNTKCQTP linear epitope on H5N1 haemagglutinin for Avian Influenza - Simson Tarigan; . Sumarningsih (Jurnal Ilmu Ternak dan Veteriner, 2016)
Rapid diagnostic tools or point-of-care (POC) test is needed in the effort to control and eradicate the high pathogenic avian influenza (HPAI) H5N1 in Indonesia. Accuracy of a POC test is determined by the specificity of antibodies, which is the main component of a POC test. Recently a linear epitope, CNTCKQTP epitope, located at 274-281 amino acid residue of H5 hemagglutinin has been confirmed to be present all clade of H5N1 viruses. This study aimed at producing and evaluating the reactivity of a monospecific, polyclonal antibody against the epitope. The Antibody was produced by immunising a goat with the peptide in the form of multiple antigen peptide (MAP). The specificity of the antibody was estimated by assaying its reactivity against influenza virus subtypes H3N3, H4N4, H5N1, H6N5, H7N7, H9N2, H10N7 and H11N9; and recombinant hemagglutinins H1-H12, H14 and H15 with ELISA and immunoblot. The results of the assay showed that CNTKCQTP antibody was not specific for H5 haemagglutinin because it cross-reacted with other haemagglutinins especially H7, H8 and H9. The potential of the peptide containing the epitope, GNCNTKCQTPMGAINSS. as an ELISA reagent for assaying H5 antibodies in chickens previously vaccinated and challenged with the H5N1 virus was also evaluated in this study. In contrast, the results of previous studies, the ELISA using GNCNTKCQTPMGAINSS as coating antigen was not sensitive in detecting antibody to haemagglutinin H5 in chickens.Key Words: AI Virus, Hemagglutinin H5, CNTKCQTP Epitope, MAP, Immunoassay